Assessment as Learning as a Strategy for Joyful Learning in Language Education - SWASTIKA, KINANTI (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This literature review aims to describe and analyze the role of Assessment as Learning (AaL) in supporting the creation of Joyful Learning within the language education context. Assessment as Learning emphasizes the active involvement of students in the assessment process, encouraging them to engage in self-reflection, monitor their own learning progress, and develop a sense of responsibility for their learning outcomes. Through this approach, teachers shift from being mere assessors to becoming facilitators and learning partners who guide students in understanding their strengths, challenges, and strategies for continuous improvement. The concept of Joyful Learning, which promotes a positive, inclusive, and motivating learning atmosphere, aligns closely with the practice of AaL, as both position students as active agents in the learning process. This literature study reviews relevant theories, practical implementations, and empirical findings related to AaL in various educational contexts, including supporting factors, implementation challenges, and effective strategies for integration. The findings of this review are expected to provide valuable insights for teachers in designing assessment systems that are more participatory, reflective, and capable of fostering an enjoyable learning experience. Keywords: Assessment as Learning, Joyful Learning, formative assessment, self-reflection, literature review.